Fetal Cholelithiasis - A Case Series - Shukla, Anil Kumar; Reddy, Ajit Kumar (Asian Journal of Medical Radiological Research, 2022)
We do not come across many cases of fetal gall stones. Our aim of the study is to discuss the ultrasonographic algorithm that we followed evaluating fetuses during pregnancy and after birth. We also evaluated the mothers gall bladder during pregnancy and postpartum. We imaged newborns where we found gall stones, for whom antenatal scan done elsewhere did not mention about it. Our purpose is to follow an algorithm for fetuses having gall stones and their mothers.